Plasmonics with two-dimensional semiconductors: from basic research to technological applications. Issue 19 (9th May 2018) - Agarwal, Amit; Vitiello, Miriam S.; Viti, Leonardo; Cupolillo, Anna; Politano, Antonio
Abstract : Herein, we discuss the features, applications, open challenges and prospects of plasmonics with various classes of two-dimensional semiconductors "beyond graphene". Abstract : Herein, we explore the main features and the prospect of plasmonics with two-dimensional semiconductors. Plasmonic modes in each class of van der Waals semiconductors have their own peculiarities, along with potential technological capabilities. Plasmons of transition-metal dichalcogenides share features typical of graphene, due to their honeycomb structure, but with damping processes dominated by intraband rather than interband transitions, unlike graphene. Spin–orbit coupling strongly affects the plasmonic spectrum of buckled honeycomb lattices (silicene and germanene), while the anisotropic lattice of phosphorene determines different propagation of plasmons along the armchair and zigzag directions. Black phosphorus is also a suitable material for ultrafast plasmonics, for which the active plasmonic response can be initiated by photoexcitation with femtosecond pulses. We also review existing applications of plasmonics with two-dimensional materials in the fields of thermoplasmonics, biosensing, and plasma-wave Terahertz detection. Finally, we consider the capabilities of van der Waals heterostructures for innovative low-loss plasmonic devices.